A standardised approach for the dispersion of titanium dioxide nanoparticles in biological media. Issue 4 (June 2013) - Taurozzi, Julian S.; Hackley, Vincent A.; Wiesner, Mark R.
Abstract We describe a comprehensive optimisation study culminating in a standardised and validated approach for the preparation of titanium dioxide (TiO2) nanoparticle dispersions in relevant biological media. This study utilises a TiO2 reference nanomaterial based on a commercially available powder that has been widely examined in both acute and chronic toxicity studies. The dispersion approach as presented here satisfies four key harmonisation requirements not previously addressed: (1) method transferability, based in part on the use of a sonication energy calibration method that allows for power measurement and reporting in a device-independent manner; (2) optimisation of sonication parameters and thorough method validation in terms of particle size distribution, pH, isoelectric point, concentration range and batch variability; (3) minimisation of sonolysis side effects by elimination of organics during sonication and (4) characterisation of nanoparticle agglomeration under various dispersion conditions by use of laser diffraction spectrometry, an in situ size characterisation technique that provides advantages over other techniques more commonly employed within the context of nanotoxicology (e.g. dynamic light scattering). The described procedure yields monomodal, nanoscale, protein-stabilised nanoparticle dispersions in biological media that remain stable for at least 48 h (acute testing timeframe) under typical incubation conditions.